Resistance and germination of spores of Bacillus species lacking members of a spore integral inner membrane protein family and locations of these proteins in spores. - Khan, Shermeen; Wicander, James; Korza, George; Caldbeck, Rebecca; Cowan, Ann E; Christie, Graham; Setlow, Peter (American Society for Microbiology, 2025)
Spores of Bacillus species are dormant and resistant to heat and chemicals but "return to life" in germination, and cells of some species/strains can cause food spoilage or disease. Recently, two members of a family of five spore integral inner membrane (IM) small protein homologs were found to be important in B. subtilis spore resistance and germination. Among these IM proteins, YetF is the most abundant. In the current work, we show that loss of any of these five homologs decreased spore resistance to heat and chemicals, with greater decreases when multiple homologs were absent. In addition, B. subtilis spores' loss of YetF and its homologs decreased the rates of spore germination, whereas loss of the second most abundant homolog, YrbG, increased germination rates. Surprisingly, B. subtilis spores lacking YetF and YrbG germinated spontaneously early in sporulation. Although this spontaneous germination did not involve normal germinant receptors or cortex peptidoglycan lytic enzymes, it was accelerated by overexpression of the IM channel for CaDPA release in germination. Loss of various homologs increased IM fluidity significantly, perhaps important in the effects of these proteins on spore resistance and germination. Notably, a functional YetF-GFP fusion was located in 5-7 IM spots in wild-type B. subtilis spores and in spores lacking the coat and outer membrane, although the function of these YetF spots is not clear. Similar spots were observed in Bacillus megaterium YetF-GFP spores, whereas ydfS null spores showed decreased wet heat resistance. Clearly, these novel proteins may have more surprises in store!IMPORTANCESpores of Bacillota are vectors for food spoilage and disease, and are hard to kill, as B. subtilis spores are killed only slowly by wet heat at 90°C. Multiple factors contribute to spores' wet heat resistance, including low spore core water content and DNA-protective proteins. Recently, a group of spore-specific inner membrane (IM) proteins was identified as increasing IM rigidity and spore wet heat resistance. B. subtilis has five of these proteins, with multiple homologs in all Bacillus and Clostridium species. These proteins increase IM rigidity, which increases spore wet heat resistance and can either increase or decrease the rates of spore germination, with similar effects on B. megaterium spores. These proteins are thus a new factor important in spore properties.
Keywords: Bacillus megaterium; Bacillus subtilis; membrane fluidity; spore germination; spore resistance; spores